Supply Chain Risikomanagement: Analyse des Status Quo und neuer Entwicklungstendenzen - Nils Alexander Zimmermann; Jens Gericke (readbox unipress, 2018)
– Supply Chain Management (SCM) and Risk Management (RM) are two current business management approaches that are based on relatively long historical developments. RM has been steadily developing since the middle of the 20th century while SCM, which started in the early 1990s, is a more recent approach in comparison. In terms of economics both approaches have been well-researched both theoretically as well as practically and variety of models have already been developed and published. Using a quantitative literature analysis, it can be shown how the number of scientific publications covering SCM and RM have increased over the years and that both are established management approaches.
Keywords: 650; Lieferkette; Risikomanagement